The economics of biodiversity the Dasgupta review - Dasgupta, Partha (Cambridge : Cambridge University Press, 2024)
"This landmark report explains the current state of play in relation to biodiversity loss and explores the ways in which we can find a sustainable path to deal with this problem, one that will require us to change how we think, act and measure success"--
Includes bibliographical references and index.
Keywords: Biodiversity conservation -- Economic aspects; Biodiversity -- Economic aspects; Environmental economics; Ecosystem health; Environmental ethics